2019
DOI: 10.1097/rlu.0000000000002751
|View full text |Cite
|
Sign up to set email alerts
|

18F-THK5351 PET Can Identify Astrogliosis in Multiple Sclerosis Plaques

Abstract: A 26-year-old woman with relapsing-remitting multiple sclerosis (MS) underwent 18F-THK5351 PET during a remission period. PET imaging showed that small regions with elevated uptake of 18F-THK5351 were scattered in the brain and that the foci of 18F-THK5351 accumulations corresponded anatomically to MS plaques identified by MRI. Because 18F-THK5351 binds to monoamine oxidase B highly expressed in astrocytes, 18F-THK5351 accumulates in lesions undergoing astrogliosis. Hence, elevated uptake of 18F-THK5351 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…Therefore, regional changes in MAO-B concentration can be an index of astrocyte reactivity, known as “astrogliosis”. These findings suggest that 18 F-THK5351 accumulates in lesions where astrogliosis occurs, and that 18 F-THK5351 PET can be a powerful biomarker for visualizing and quantifying astrogliosis, as recently demonstrated in patients with neurological disorders [ 10 13 ]. More importantly, longitudinal assessment of the degree of astrogliosis in the living human brain can provide new insights into the pathophysiology of neurological disorders.…”
Section: Introductionsupporting
confidence: 64%
“…Therefore, regional changes in MAO-B concentration can be an index of astrocyte reactivity, known as “astrogliosis”. These findings suggest that 18 F-THK5351 accumulates in lesions where astrogliosis occurs, and that 18 F-THK5351 PET can be a powerful biomarker for visualizing and quantifying astrogliosis, as recently demonstrated in patients with neurological disorders [ 10 13 ]. More importantly, longitudinal assessment of the degree of astrogliosis in the living human brain can provide new insights into the pathophysiology of neurological disorders.…”
Section: Introductionsupporting
confidence: 64%
“…Clinical 18 F-THK-5351 PET studies demonstrated high tracer retention in sites susceptible to astrogliosis in various neurodegenerative conditions (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The non-selective binding of THK-5351 to MAO-B and tau limits its clinical utility as a biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study on patients affected by corticobasal syndrome, [18F]THK5351 binding have been demonstrated to detect dynamical astrogliosis in specific cortical regions (Ezura et al, 2019). In a case of multiple sclerosis, instead, the authors demonstrated the coregistration of [18F]THK5351 uptake with demyelinating plaques (Ishibashi et al, 2019). Another study compared the spatial uptake patterns of [18F]THK5351 and fMRI network alterations in patients with early AD and healthy controls, showing a similar pattern for the precuneus, a region crucial for Alzheimer progression (Yokoi et al, 2018).…”
Section: Pet and Mr Imaging Of Astrocytic Activationmentioning
confidence: 99%
“…Compared to microglial visualization, PET radiotracers specific for astrocytic function have been only recently applied for clinical purpose, mainly binding the mono-amine oxidase type B (MAOB) enzyme, highly expressed by activated astrocytes (Table 1) (Figure 2) (Ishibashi et al, 2019). PET studies using the MAOB radiotracers 11C-DED or [18F]THK5351 in patients affected by Alzheimer's disease have demonstrated an high correlation between brain tau deposition and astrocytic uptake and between cortical glucose hypometabolism, detected by 18F-fluorodeoxyglucose [18F]-FDG PET, and longitudinal decline in astrocytic function detected by 11C-DED (Carter et al, 2019).…”
Section: Pet and Mr Imaging Of Astrocytic Activationmentioning
confidence: 99%
See 1 more Smart Citation